Determinant Analysis of Education Inequalities in Indonesia - Evi Syuriani Harahap; Indra Maipita; M. Fitri Rahmadana (Budapest International Research and Critics University, 2020)
Education is the main capital for humans to prosper. The importance of the role of education in improving welfare requires the need for equal distribution of education in each region regardless of socioeconomic, gender and racial backgrounds. In making educational equality, it is important to know the factors that influence educational inequality, namely income inequality, poverty and education gap. Reducing the income inequality, poverty and education gender gap in each province in Indonesia will reduce education inequality which is the responsibility of all parties, both the central and regional governments. The purpose of this study is to analyze the effect of income inequality, poverty and education gender gap on education inequality in Indonesia in 2016-2018. Data analysis was performed using the Ordinary Least Square (OLS) method with a panel data regression estimation model using the help of eviews 9.0. Estimation results show that partially income inequality, poverty and gender gap in education have a positive and significant effect on educational inequality in Indonesia, while simultaneously income inequality, poverty and education gender gap negatively affect education inequality in Indonesia.